The ultradian rhythm of glucocorticoid secretion and the time course of target gene regulation - V. M. Merkulov; N. V. Klimova; T. I. Merkulova (Вавиловский журнал генетики и селекции)
Glucocorticoid hormones (cortisol in humans and corticosterone in rodents) are secreted in discrete pulses during a day with a periodicityof approximately 1 h (ultradian rhythm), and this pattern is also maintained in plasma and extracellular fluid. However, the vast majority of studies on gene regulation by glucocorticoids typically assess gene responses regardless the ultradian rhythm. These experiments are usually performed using long-term stimulation with synthetic hormones (dexamethasone and triamcinolone), which form much more stable complexes with glucocorticoid receptor (GR) then natural hormones. This review summarizes the current scarce information, obtained in experiments mimicking the ultradian mode of natural hormone secretion in cultured cells and in animal models. The results of these experiments clearly demonstrate that ultradian stimulation by natural hormones induces rapid GR exchange with glucocorticoid response elements and leads to cyclic GR mediated transcriptional regulation (gene pulsing) at the level of nascent RNA. In contrast, synthetic glucocorticoids, having much higher receptor affinity, fail to disengage from nuclear receptors with sufficient speed to support the ultradian cycles, thereby uncoupling extracellular hormone fluctuations from appropriate receptor function at response elements. This alters RNA accumulation profiles dramatically. These findings suggest potentially important consequences of ultradian secretion. The transcriptional program induced by hormone pulses differs significantly from that generated by constant hormone treatment. Thus, treatment with synthetic glucocorticoids may not provide an accurate assessment of physiological hormone action.